2000
DOI: 10.1103/physrevlett.84.3482
|View full text |Cite
|
Sign up to set email alerts
|

Multipartite Entanglement for Continuous Variables: A Quantum Teleportation Network

Abstract: We show that one single-mode squeezed state distributed among N parties using linear optics suffices to produce a truly N -partite entangled state for any nonzero squeezing and arbitrarily many parties. From this N -partite entangled state, via quadrature measurements of N − 2 modes, bipartite entanglement between any two of the N parties can be 'distilled', which enables quantum teleportation with an experimentally determinable fidelity better than could be achieved in any classical scheme.PACS numbers: 03.6… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
521
1
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 525 publications
(531 citation statements)
references
References 20 publications
6
521
1
3
Order By: Relevance
“…It has been shown how to produce genuinely entangled multimode states by van Loock and Braunstein [29]. We now want to give some simple conditions for determining whether a three-mode state is genuinely entangled, and to give an example of such a state that is not Gaussian and whose entanglement can be demonstrated by these conditions.…”
Section: Three-mode Entanglementmentioning
confidence: 99%
“…It has been shown how to produce genuinely entangled multimode states by van Loock and Braunstein [29]. We now want to give some simple conditions for determining whether a three-mode state is genuinely entangled, and to give an example of such a state that is not Gaussian and whose entanglement can be demonstrated by these conditions.…”
Section: Three-mode Entanglementmentioning
confidence: 99%
“…Teleportation of quantum entanglement, i.e., entanglement swapping has been also realized [9,10]. Furthermore, CV teleportation has been extended to a multipartite protocol known as a quantum teleportation network [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The study of CV multipartite entanglement was initiated in [23,24], where a scheme was suggested to create pure CV N -party entanglement using squeezed light and N −1 beamsplitters. In fact, this discussion indicates that tripartite entanglement has already been created (though not investigated or detected) in the CV quantum teleportation experiment [14].…”
Section: Introductionmentioning
confidence: 99%